PERAN BRAND IMAGE MEMEDIASI PENGARUH ELECTRONIC WORD OF MOUTH (E-WOM) DAN SERVICE QUALITY TERHADAP REPURCHASE INTENTION DOMUS COFFEE & EATERY - Herru Wijaya; Ni Ketut Seminari (BORJUIS: JURNAL OF ECONOMY, 2025)
The coffee shop industry in Indonesia has grown significantly, driven by globalization and Generation Z’s preference for aesthetic and social spaces. This study aims to analyze the influence of electronic word-of-mouth (E-WOM) and service quality on repurchase intention, with brand image as a mediating variable, among consumers of Domus Coffee & Eatery in Denpasar. Using a quantitative approach grounded in the Stimulus-Organism-Response (SOR) theory, data were collected from 120 respondents through questionnaires, observations, interviews, and documentation. Path analysis results indicate that both E-WOM and service quality positively and significantly affect brand image and repurchase intention, directly and indirectly through brand image mediation. Service quality had the strongest total effect (β = 0.541) compared to E-WOM (β = 0.278), making it the dominant factor influencing repeat purchase behavior. These findings highlight the importance of digital reputation management and consistent service delivery in building a strong brand image and maintaining customer loyalty, especially amidst intense competition in Denpasar’s coffee shop industry.